Metal single‐atom‐confined electrocatalysts to water oxidation: Development, innovation, and challenges. Issue 4 (12th July 2021) - Zhang, Ling; Shi, Yuhe; Li, Lin; Wang, Ling; Han, Jing Long; Wang, Ai Jie
Abstract: In this review, we address the progress of single‐atom‐confined electrocatalysts toward water oxidation in synthetic methods, catalytic mechanisms, and structural analysis. It emphasizes the vital role of special defective structures of transition metal hydroxide/oxide matrix materials in stabilizing the noble metal single atoms and the coordination role of metal single atoms with N, S atoms in a matrix in improving the catalytic activity toward water oxidation. In part 1, the development of single‐atom‐confined electrocatalysts is described. In part 2, noble metal single‐atom‐confined electrocatalysts with transition metal hydroxide/oxide, carbon materials, and noble metal alloy as the supports are detailed. In part 3, transition metal single‐atom‐confined carbon matrix electrocatalysts and transition metal complex composed crystal electrocatalysts are introduced. In part 4, the challenges in synthetic strategy, catalytic activity, and stability of varying metal single atoms catalysts are laid out. Abstract : This review lays out the most recent development of electrocatalysts toward water oxidation based on metal single atoms, including synthetic methods, catalytic mechanisms, and structural analysis.